2015
DOI: 10.1080/00038628.2014.1002828
|View full text |Cite
|
Sign up to set email alerts
|

Air conditioning and the neutral temperature of the Indonesian university students

Abstract: Recent thermal comfort studies conducted in two private universities, namely Universitas Tarumanagara (Untar) and Universitas Mercu Buana (UMB) in Jakarta, Indonesia, showed a result that is fairly different from the previous thermal comfort studies carried out in this country. This study involved 90 students and collected 900 thermal votes. Students' comfort temperature in both universities was significantly lower than the previous comfort study conducted in Jakarta (1993), and it was almost similar compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…• The comparative study on thermal comfort conducted in Jakarta and Bandung is shown in table 5. There are some differences in the calculation results of the office buildings in Jakarta and the college buildings in Bandung [20]. The smallest difference is found from the study conducted on the college buildings at the neutral temperature using air temperature between 24.7 o C and 24.47 o C with a deviation of only 0.23 o C. The most significant difference between 27.2 o C and 24.17 o C is found in the neutral temperature using the operative temperature at the office buildings in Jakarta with the distinction of the only 3.03 o C. This research has a reasonable consideration as it is conducted in mountainous areas with lower average temperatures than those conducted in Jakarta and Bandung.…”
Section: Results S and Discussionmentioning
confidence: 99%
“…• The comparative study on thermal comfort conducted in Jakarta and Bandung is shown in table 5. There are some differences in the calculation results of the office buildings in Jakarta and the college buildings in Bandung [20]. The smallest difference is found from the study conducted on the college buildings at the neutral temperature using air temperature between 24.7 o C and 24.47 o C with a deviation of only 0.23 o C. The most significant difference between 27.2 o C and 24.17 o C is found in the neutral temperature using the operative temperature at the office buildings in Jakarta with the distinction of the only 3.03 o C. This research has a reasonable consideration as it is conducted in mountainous areas with lower average temperatures than those conducted in Jakarta and Bandung.…”
Section: Results S and Discussionmentioning
confidence: 99%
“…The comfort temperature of the subjects was found to be 24.1 °C. The average daily temperature in this area is about 28.5 °C [7].…”
Section: Thermal Comfort Studies Of Students In Tarumanagara Universimentioning
confidence: 99%
“…Some of 432 thermal votes were collected during the longitudinal surveys. Subjects were comfortable at 24.9 °C [7].…”
Section: Thermal Comfort Studies Of Students In Mercu Buana Universitmentioning
confidence: 99%
“…Tabulation and analysis process of TSV's data and climatic parameters data were conducted by statistical test and linier regression analyses to achieve the ward's user thermal comfort level [22], [23].…”
Section: B Ward's Thermal Performance and Its Architecture Design Asmentioning
confidence: 99%